Role of Tb-Cr Substitution on the Structural and Magnetic Properties of Cobalt Ferrites - Hameed, Abdul; Khaliq, Muhammad Waqas (Journal of Materials and Physical Sciences, 2021)
The impact of Tb-Cr substitution in cobalt-based ferrites having composition Co1-xTbxFe2-yCryO4 (x=0.0-0.1, y=0.0-0.5) prepared by solid state reaction method on structural, magnetic and dielectric parameters was explored. Structural analysis was carried out by X-ray diffraction technique. A variation in lattice parameter (a) was observed as a function of doping. The lattice constant ‘a’ increases from 8.37 Å to 8.39 Å, whereas crystallite size (D) decreases from 44 nm to 28 nm with Tb-Cr substitution. Unit cell volume was found in the range 586.8 Å3 - 590.6 Å3. X-ray density, bulk density as well as porosity were also affected with the inclusion of Tb-Cr ions. Saturation magnetization and remanence were observed to decrease from 62 emu/g to 51 emu/g and 13.38 emu/g to 8.29 emu/g, respectively with the addition of Tb-Cr contents. The incorporation of Tb-Cr cations caused the decrease in dielectric parameters like dielectric constant as well as dielectric loss.